2015
DOI: 10.1016/j.febslet.2015.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization state and pigment binding strength of the peridinin‐Chla‐protein

Abstract: a b s t r a c tThe peridinin-chlorophyll a-protein (PCP) is one of the major light harvesting complexes (LHCs) in photosynthetic dinoflagellates. We analyzed the oligomeric state of PCP isolated from the dinoflagellate Symbiodinium, which has received increasing attention in recent years because of its role in coral bleaching. Size-exclusion chromatography (SEC) and small angle neutron scattering (SANS) analysis indicated PCP exists as monomers. Native mass spectrometry (native MS) demonstrated two oligomeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…A large amount of the earliest work that leveraged the structural analysis of photosynthetic proteins with native MS was performed by the Blankenship group. , Their first attempt at using native MS to characterize the well-studied Fenna–Matthews–Olson (FMO) complex, the first pigment–protein complex with a solved crystal structure, , complemented available structural data by determining the exact number of pigment molecules bound within the complex. In their work, Wen et al took advantage of native MS to provide a snapshot of complex heterogeneity and confirmed that one of the pigments missing in hitherto available structures demonstrated partial occupancy due to surface exposure .…”
Section: Application Of High-resolution Native Ms In the Characteriza...mentioning
confidence: 99%
See 2 more Smart Citations
“…A large amount of the earliest work that leveraged the structural analysis of photosynthetic proteins with native MS was performed by the Blankenship group. , Their first attempt at using native MS to characterize the well-studied Fenna–Matthews–Olson (FMO) complex, the first pigment–protein complex with a solved crystal structure, , complemented available structural data by determining the exact number of pigment molecules bound within the complex. In their work, Wen et al took advantage of native MS to provide a snapshot of complex heterogeneity and confirmed that one of the pigments missing in hitherto available structures demonstrated partial occupancy due to surface exposure .…”
Section: Application Of High-resolution Native Ms In the Characteriza...mentioning
confidence: 99%
“…The oligomeric state, pigment content, and complex stabilities were also determined for other photoprotective proteins, like peridinin–chlorophyll–protein and fluorescent recovery protein (FRP) . By combining native MS with cross-linking MS and site-specific mutations, Lu et al proposed a novel mechanism of function for dimeric FRP, which participates in photoquenching by dissociating OCP from the PBS .…”
Section: Application Of High-resolution Native Ms In the Characteriza...mentioning
confidence: 99%
See 1 more Smart Citation
“…A large amount of the earliest work that leveraged the structural analysis of photosynthetic proteins with native MS was performed by the Blankenship group 29,[297][298][299][300][301][302][303][304] .…”
Section: Protein Assemblies Involved In Light Harvestingmentioning
confidence: 99%
“…The oligomeric state, pigment content, and complex stabilities were also determined for other photoprotective proteins, like peridinin-chlorophyll-protein 302 and the fluorescent recovery protein (FRP) 299 . By combining native MS with cross-linking MS and site-specific mutations, Lu et al proposed a novel mechanism of function for dimeric FRP, which participates in photoquenching by dissociating OCP from the PBS 300 .…”
Section: Protein Assemblies Involved In Light Harvestingmentioning
confidence: 99%